PENGARUH PEMBERIAN PUPUK MULTIFUNGSI TERHADAP PRODUKTIVITAS RUMPUT ODOT (Pennisetum Purpureum CV. MOTT) SETELAH DEFOLIASI PERTAMA - Harahap, Akhiruddin; Siswoyo, Purwo; Rusdhi, Alfath (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
The purpose of this research is to determine the effect of multifunctional fertilizer application on the productivity of Pennisetum purpureum cv. Mott grass after the first defoliation. The data analysis method used in this research is a Completely Randomized Design (CRD) Non-Factorial consisting of 4 treatments and 5 replications, namely P0 (Without multifunctional fertilizer application), P1 (Multifunctional fertilizer application every 2 days), P2 (Multifunctional fertilizer application every 3 days), and P3 (Multifunctional fertilizer application every 5 days). The parameters observed in this study are the number of tillers, plant height, and fresh material production. The results of the study show that treatment P1 is the best treatment in terms of fresh material production, plant height, and number of tillers of Pennisetum purpureum cv. Mott grass with multifunctional fertilizer application after the first defoliation, with the number of tillers of Pennisetum purpureum cv. Mott grass being 4.88/polybag, plant height being 65.40 cm/polibag, and fresh material production being 216.84 grams/polybag.